Why place matters in residential care: the mediating role of place attachment in the relation between adolescents’ rights and psychological well-being - Magalhães, E. (2020)
Little evidence exists on the relationship between rights’ perceptions and well-being outcomes during the adolescence, and particularly in care, as well as on the mediating role of place attachment. Young people in residential care are psychologically and socially vulnerable, showing greater difficulties than their peers do in the family. Youth’s rights fulfilment in residential care may positively affect their psychological functioning together with positive attachments to this place. A sample of 365 adolescents in residential care settings (M = 14.71, SD = 1.81) completed a set of self-reported measures, specifically, the Rights perceptions scale, the Place attachment scale and Scales of psychological well-being. Results revealed significant mediating effects of place attachment (Global scale and subscales of Friends Bonding and Place Dependence) on the relationship between Participation and Protection rights in residential care and Psychological well-being (Positive Relations with others, Personal Growth and Self-Acceptance). The positive role of rights fulfilment in residential care, specifically participation opportunities, as well as the role of youth’s attachment to the care setting are discussed based on previous evidence and theoretical assumptions. A set of practical implications is described.